MODEL PEMBELAJARAN ARTIKULASI DENGAN MEDIA ANIMASI POWTOON UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN AKUNTANSI KEUANGAN - Julianingrum, Ika Rahma; Muchsini, Binti; Adi, Wahyu (Prosiding Seminar Nasional Pendidikan Akuntansi dan Keuangan, 2015)
ABSTRAKTujuan penelitian ini adalah untuk mengetahui apakah penerapan model pembelajaran artikulasi dengan media animasi powtoon dapat meningkatkan prestasi belajar mata pelajaran akuntansi keuangan. Penelitian ini merupakan penelitian tindakan kelas (PTK). Teknik pengumpulan data adalah dengan tes, observasi dan dokumentasi. Analisis data menggunakan teknik analisis kuantitatif dan analisis kualitatif. Hasil penelitian pada pratindakan prestasi belajar aspek afektif 43,75%, aspek kognitif 25% dan aspek psikomotor 50%. Pada siklus I prestasi belajar aspek afektif 56,25%, aspek kognitif 56,25% dan aspek psikomotor 62,5%. Kemudian pada siklus II prestasi belajar aspek afektif 84,38%, aspek kognitif 87,5% dan aspek psikomotor 100%. Penelitian ini menyimpulkan bahwa penerapan model pembelajaran artikulasi dengan media animasi powtoon dapat meningkatkan prestasi belajar mata pelajaran akuntansi keuangan.Â Â ABSTRACTÂ The objective of the research is to investigate whether the application of the articulation learning model with Powtoon animation media can improve the learning achievement in the Financial Accounting. This research used the class room action research (CAR). The data of research were collected through test, observation, and documentation/archives. They were analyzed by using the quantitative and qualitative analysis. The result of the research shows that in prior to the treatment in Pre-cycle, the studentsâ learning achievement on the affective aspect was 43.75% in the studentsâ learning achievement on the cognitive aspect was 25%, and the studentsâ learning achievement on the psychomotor aspect was 50%. Following the treatment in Cycle I, the studentsâ learning achievement on the affective aspect became 56.25%, the studentsâ learning achievement on the cognitive aspect became 56.25%, and the studentsâ learning achievement on the psychomotor aspect was 62.5%. In addition, in Cycle II, the studentsâ learning achievement on the affective aspect became 84.38%, the studentsâ learning achievement on the cognitive aspect became 87.5%, and the studentsâ learning achievement on the psychomotor aspect became 100%. Thus, the application of the articulation learning model with Powtoon animation media can improve the learning achievement on the Financial Accounting.Â Â Kata kunci: prestasi belajar, model pembelajaran artikulasi dan media animasi powtoonÂ